Resveratrol improves bone repair by modulation of bone morphogenetic proteins and osteopontin gene expression in rats - Casarin, R. C. [UNESP]; Casati, M. Z. [UNESP]; Pimentel, S. P. [UNESP]; Cirano, F. R. [UNESP]; Algayer, M. [UNESP]; Pires, P. R. [UNESP]; Ghiraldini, B. [UNESP]; Duarte, P. M.; Ribeiro, F. V. [UNESP] (Churchill Livingstone, 2014)
This study investigated the effect of resveratrol on bone healing and its influence on the gene expression of osteogenic markers. Two calvarial defects were created and one screw-shaped titanium implant was inserted in the tibia of rats that were assigned to daily administration of placebo (control group, n = 15) or 10 mg/kg of resveratrol (RESV group, n = 15) for 30 days. The animals were then sacrificed. One of the calvarial defects was processed for histomorphometric analysis and the tissue relative to the other was collected for mRNA quantification of bone morphogenetic protein (BMP)-2, BMP-7, osteopontin (OPN), bone sialoprotein (BSP), osteoprotegrin (OPG), and receptor activator of NF-kappa B ligand (RANKL). Implants were removed by applying a counter-torque force. Histomorphometric analysis revealed higher remaining defect in the calvarial defects of the control group than the RESV group (P = 0.026). Resveratrol increased the counter-torque values of implant removal when compared to control therapy (P = 0.031). Gene expression analysis showed a higher expression of BMP-2 (P = 0.011), BMP-7 (P = 0.049), and OPN (P = 0.002) genes in the RESV group than in the control group. In conclusion, resveratrol improved the repair of critical-sized bone defects and the biomechanical retention of implants. Indeed, this natural agent may up-regulate the gene expression of important osteogenic markers.
Keywords: Resveratrol; Plants; Medicinal; Wound healing; Rats; Osseointegration; Gene expression